Patterns of Ironic Metaphors in Lithuanian Politicized Discourse - Vengalienė, Dovilė (Respectus Philologicus, 2019)
[full article and abstract in English] The present article is an attempt to examine the metaphoric models of ironic assessment employed in politicized public discourse in Lithuania. The examination follows the implications of the Blending theory (Fauconnier & Turner 2002), and discusses the topicality of the dominant metaphoric patterns in online newspaper headlines and commentaries, as well as in a number of posters the political parties of Lithuania prepared for the electoral campaign. The database of 200 newspaper headlines, comments, and posters allowed to identify dominant references to political issues in terms of sport, miracles, family, business and crime. Furthermore, the analysis has shown that attention should be drawn to aspects of social cognition and culture as they appear to be an integral part of the blending structure and are crucial in successful transmission of both the intended message and the evaluative attitude. Metaphors in the mode of irony follow a double-scope conceptual integration network, as the final blend comprises not only the elements of the two input spaces of the employed metaphor but also the elements of our background knowledge.